Banded iron formation to iron ore: a record of the evolution of Earth environments? - Evans, Katy; McCuaig, T.; Leach, D.; Angerer, T.; Hagemann, S. (Geological Society of America, 2013)
Banded iron formations (BIF) are the protolith to most of the world’s largest iron ore deposits. Previous hypogene genetic models for Paleoproterozoic “Lake Superior” BIF-hosted deposits invoke upwards, down-temperature flow of basinal brines via complex silica and carbonate precipitation/dissolution processes. Such models are challenged by the necessary SiO2 removal. Thermodynamic and mass balance constraints are used to refine conceptual models of the formation of BIF-hosted iron-ore. These constraints, plus existing isotope and halogen ratio evidence, are consistent with removal of silica by down- or up-directed infiltration of high-pH hypersaline brines, with or without a contribution from basinal brines. The proposed link to surface environments suggest that Paleoproterozoic BIF-ore upgrade may provide a record of a critical time in the evolution of the Earth’s biosphere and hydrosphere.